Pengaruh Biaya Produksi dan Biaya Penjualan Terhadap Laba pada UMKM Konveksi “Ade Jahit” di Desa Anggadita - Elvina Dwitianti; Sihabudin; Robby Fauji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to strengthen the relationship between production and sales costs and profits at the "ade sewing" MSME convection. One of the businesses that provides clothing production services is the "ade sewing" convection which is located in Anggadita village, Kec. Explain. Hypothesis testing The t test, F, and coefficient of determination (R2) coefficient of determination (R2), t test, and F test are three multiple linear regression analysis instruments used in the quantitative descriptive method of this research. This research focuses on MSMEs that use "ade sewing" convection. The results of the research show that in convective "sewing" MSMEs, production costs have a significant effect on income as indicated by a t test value of 3.257 > t 1.997 and a significance level of 0.004 < 0.005. At the significance threshold of 0.001 < 0.005, sales costs have quite a large influence on profits, this is indicated by the t test findings of 4.054 > 1.977 t. With a determined f value of 34.826 > 3.13 and a significance level of 0.000 < 0.005, production and sales costs have a fairly large influence on profitability.